Eco - Handloom Weaver: Retailers Perspective In New Product Development Hiou Simalungun - Liharman Saragih; Yanti Jesika Nasution; Vina Depi Cintya Ginting; Carolin Agrifa Manik (Manajemen: Jurnal Ekonomi USI, 2024)
The article aims to explore new product development, particularly in the Hiou industry in Simalungun, by involving various instruments that consist of new product development strategies, development processes, organizational relationships with new product development, and the evaluation of new product performance itself. The research results show that 57.14% of respondents agree that New Product Development is aimed at meeting the demands of traders, and the Objective of New Product Development is to meet the demands of traders, with 32.14% agreeing and 40% agreeing that new product development is carried out after obtaining approval from external parties